(untitled) (Bangladesh Journal of Urology, 2020)
Aims and objective : To evaluate the safety and efficacy of supracostal puncture for PCNL procedure. Materials and methods : This is a retrospective study conducted in Department of Urology, NIKDU, Dhaka, from January 2013 to December 2016. A total of 408 patients underwent PCNL, of whom 56 (13.72%) had supracostal access. All procedures were performed under G/A. All were performed in a single setting & the data were analysed for indications, stone clearance rates and the complications associated with supracostal access. The indications for supracostal access were staghorncalculi ,uppercalyceal stone, pelvic stone , complex inferior calyceal stones , stones in upper ureter and high lying kidney. All supracostal punctures were made in 11th intercostal space and was made by the urologists under C- arm fluoroscopic guidance in prone position. After tract dilatation ultrasound lithotripsy was used for fragmentation of stones. The operative time , success rate, hospital stay and complications were evaluated. Results : Single tract access was used in 44 (78%) cases, 12 (22%) patients required a second tract. Additional punctures were needed for staghorn calculi (4 out of 14). Overall 82% of the patients were rendered stone free or had a clinically insignificant residual calculi with PCNL alone and this increased to 96% with ancillary procedures. In patient with staghorn calculi, they were completely cleared in 78%. Overall complication rate was 26% which included hydrothorax in 5 (10%) patients,3 of which required insertion of chest tube. 2 (3.5%) patient developed haemothorax due to injury to intercostals vessels, 2 (3.5%) patient developed perforation of the pelvis, 2(3.5%) developed perinephric collection, infection/ urosepsis in 4(7%). The rest of the patients recovered successfully. Post operative stay ranged from 2 to 9 days. Conclusion : Supra costal puncture is safe and effective option which give high stone clearance rate with acceptable complications. With a good understanding of the anatomy surrounding the upper pole of the kidney and attention to a few technical considerations during the procedures, access is very safe and effective. Bangladesh Journal of Urology, Vol. 21, No. 2, July 2018 p.140-144